Compassionate design for dementia care. Issue 3 (3rd July 2019) - Treadaway, Cathy; Taylor, Aidan; Fennell, Jac
ABSTRACT: One of the most pressing challenges facing designers today is how to create appropriate, useful and safe designs for people living with advanced dementia. Dementia is a complex disease that presents and progresses differently for each individual. This paper contends that co-design with experts, including people living with dementia and their carers, is essential to inform design. Compassionate Design principles are useful to guide the creative process and ensure that concepts are developed that maintain the dignity, personhood and wellbeing of the person living with dementia. The key themes of Compassionate Design are presented through examples of designs for playful objects created as part of the LAUGH design for dementia research. A qualitative participatory co-design research methodology is described along with findings informed by a Live Lab evaluation of the objects with people living with advanced dementia living in residential care.